Screening for the Sickle Cell Trait in Schools is more Efficient than during the Pre-Nuptial Period for the Prevention of Sickle Cell Anemia in a Sub-Saharan Africa Country. [Sickle Cell Trait Scree-ning and Sickle Cell Anemia Prevention in Sub-Saharan Africa] - Muteb, Paul Boma; Luntadila, Stéphanie Ngimbi; Maurice, Ndeme Bongali; Mamba, Jean Fidèle Kaluila; Magwandji, Ada Kalunda; Mulefu, Jules Panda; Somwe, Somwe Wa; Diallo, Dapa Aly (Journal of Hematology Research, 2019)
Sickle cell disease is a hereditary disease of hemoglobin which has been declared a public health priority by international health decision-making institutions. Among strategies to combat this disease, WHO recommends a reduction of births with sickle cell anemia through awareness and screening for the sickle cell gene in countries where the sickle cell gene is prevalent. Approaches to make this strategy efficient in Sub-Saharan Africa have not been studied. This study aim was to evaluate the efficacy of screening for the sickle cell gene for the primary prevention of sickle cell anemia among two target populations in a country of Sub-Saharan Africa. This was a prospective study comprising a free and voluntary screening for the sickle cell gene at various intervals, then to evaluate the impact of the screening on engagement or marriage decision-making on two target populations following raising awareness of sickle cell disease. Data was collected through a questionnaire administered at the headquarters of the NGO SS Assistance in Lubumbashi or by phone. 136 pupils with SCT and 111 married couples despite being screened for SCT during engagement were the subject of the study. In the target group of 136 SCT carriers (AS) in schools, 49 (48%) were married with an AA partner, 53 were engaged among whom 42 with an AA partner, 3 with an AS partner and 8 with a partner with an undetermined hemoglobin phenotype, 34 did not have any commitment. 91 (67%) pupils with SCT avoided a risk for SCA birth. Among the 111 couples married despite their screening as SCT carriers during pre-marital tests, 7 (6, 3%) have not registered SCA birth but 104 (93.7%) had 141 SCA births (extremes: 1 and 3 per couple). Sickle cell gene screening in a population without engagement or marriage plans is more productive than that conducted in the prenuptial period. However, results highlight the need to conduct more studies on sickle cell gene screening in Sub-Saharan Africa with the best strategies to reduce the psychological, social and economic burden of such studies especially when adults are targeted.